Association between cardioplegia and postoperative atrial fibrillation in coronary surgery. (1st February 2021) - Mauro, Michele Di; Calafiore, Antonio M.; Di Franco, Antonino; Nicolini, Francesco; Formica, Francesco; Scrofani, Roberto; Antona, Carlo; Messina, Antonio; Troise, Giovanni; Mariscalco, Giovanni; Beghi, Cesare; De Bonis, Michele; et al.
Abstract: Objective: The aim of this multicenter study was to evaluated whether cold or warm cardioplegia are associated with postoperative atrial fibrillation (POAF) and the prognostic role of the latter on early stroke and neurological mortality. Method: This was a retrospective analysis of prospective collected data from 9 cardiac centers in Italy and the United States including patients undergoing surgery between 2010 and 2018. From the 9 institutional databases, 17, 231 patients underwent isolated CABG on-pump, using either warm cardioplegia ( n  = 7730) or cold cardioplegia ( n  = 9501); among the latter group blood and crystalloid cardioplegia were used in 691 and 8810 patients, respectively. After matching, two pairs of 4162 patients (overall cohort 8324) were analyzed. Results: In matched population, the rate of POAF was 18% (1472 cases), 15% (608) in warm group versus 21% (864) in cold group ( p  < 0.001). Multivariable analysis confirmed that cold cardioplegia was associated with higher rate of POAF, along with age, hypercholesterolemia, LVEF, reoperation, preoperative IABP, previous stroke, cardiopulmonary and cross-clamp. Moreover, cold cardioplegia as well as POAF increased the rate of postoperative stroke as well as early mortality and neurological mortality Propensity-weighted cohort included 11, 830 (70%) patients out of 17, 231. After adjustment, both cold blood and cold crystalloid cardioplegia negatively influenced POAF, stroke and neurological mortality. Conclusions: Warm cardioplegia may reduce the rate of POAF in CABG patients with respect to cold cardioplegia, either blood or crystalloid. This has a prognostic impact on postoperative stroke and neurological mortality. Graphical abstract: Unlabelled Image Highlights: Warm cardioplegia may reduce the rate of POAF in CABG patients. Other risk factors for POAF were age, LVEF, IABP, hypercholesterolemia, redo. Cold cardioplegia is associated with worse early outcome. POAF is associated with worse early outcome.